Uji Kualitas Pupuk Organik Cair Limbah Biodigester Dari Area Kuliner Cimanuk, Indramayu Jawa Barat - Asad, Faisal Al; Dwimartina, Fina; Carsidi, Didi; Santoso, Teguh Iman (Jurnal Agro Wiralodra, 2025)
A biodigester is a device or closed container containing fermented organic materials to produce gas and organic matter. One of the organic materials produced by a biodigester is liquid waste. Liquid waste from a biodigester can be used as liquid organic fertilizer (POC). All organic materials can be used as raw materials for biodigester fermentation. One of the organic materials utilized is organic waste from food and beverage waste. The biodigester in the Cimanuk Culinary Area, Indramayu, West Java, operates by utilizing the surrounding food and beverage waste. The purpose of this study was to utilize the potential of biodigester waste as POC. The study was conducted using an experimental method, namely making POC from organic waste originating from the Cimanuk Culinary Area, Indramayu, West Java, which was put into the biodigester. The POC produced from the biodigester was chemically analyzed to determine the content of N, P, K, organic C, and pH. The results of chemical analysis show that the Liquid Organic Fertilizer (POC) produced contains nitrogen (N), phosphorus (P), potassium (K), and organic carbon (C-organic), respectively, at 0.46%, 0.02%, 0.07%, and 1.04%. All of these contents are still below the minimum quality standards as stipulated in the Decree of the Minister of Agriculture of the Republic of Indonesia Number 261 of 2019, namely N, P, K of 2–6% and C-organic at least 10%, so it is necessary to improve the quality of raw materials and the fermentation process. However, the pH value of POC of 9.1 indicates that the fertilizer is mature and chemically relatively stable